Convenient access to pyrrolidin-3-ylphosphonic acids and tetrahydro-2H-pyran-3-ylphosphonates with multiple contiguous stereocenters from nonracemic adducts of a Ni(II)-catalyzed Michael reaction - Reznikov, Alexander N.; Nikerov, Dmitry S.; Sibiryakova, Anastasiya E.; Rybakov, Victor B.; Golovin, Evgeniy V.; Klimochkin, Yuri N. (Beilstein Journal of Organic Chemistry, 2020)
A new synthetic strategy toward nonracemic phosphoryl-substituted pyrrolidines and tetrahydropyranes with three and five contiguous stereocenters is presented. Readily available β-keto phosphonates react with conjugated nitroolefins in the presence of a chiral Ni(II) complex to give nitro keto phosphonates with two stereocenters with excellent enantioselectivity and moderate to high diastereoselectivity. These products were used for a reductive cyclization leading to pyrrolidin-3-ylphosphonic acid and for reactions with aldehydes yielding tetrahydropyranylphosphonates as individual stereoisomers. These nonracemic heterocycles containing phosphoryl moieties are useful for designing new pharmacologically active compounds.
Keywords: asymmetric catalysis; Michael addition; phosphonates; pyrrolidines; tetrahydropyranes